Empirical Methods for Estimation of Reference Evapotranspiration for Codó, Maranhão, Brazil - Lopes Sobrinho, Oswaldo Palma (2024)
Reference evapotranspiration (REo) is an important parameter for planning and managing water resources. The objective of this study was to compare the reference evapotranspiration estimation methods proposed by Hargreaves-Samani, Blaney-Criddle and Priestley-Taylor in relation to the standard Penman-Monteith method for the municipality of Codó, Maranhão, Brazil. The objective of this study was to compare the reference evapotranspiration estimation methods proposed by Hargreaves-Samani, Blaney-Criddle and Priestley-Taylor in relation to the standard Penman-Monteith method for the municipality of Codó, Maranhão, Brazil. Daily values of maximum (Tmax), average (Tmed) and minimum (Tmin) air temperature, maximum (RHmax), mean (RHmed) and minimum (RHmin) relative air humidity, wind direction (Dv), radiation global solar energy (Rg), radiation balance (Rb), precipitation (P) and wind speed (W/S). To analyze the performance of the methods, the correlation coefficients (R), determination coefficients (R²) and the Willmott index (c) were considered. Throughout the year, the REo estimate using the HS method overestimated those obtained using PM, BC and PT. The same occurred with PT in relation to PM, but with a smaller magnitude. Regardless of the season of the year, the BC method presented the best data performance in relation to the standard PM-56 method and the HS method did not present good agreement for REo in the climatic conditions of Codó, MA for the summer and fall.